Multicultural Education from an Islamic Perspective: Building Intercultural Tolerance in Indonesian Primary Schools - Kholida, Siti; Niam, Syamsun; Qomar, Mujamil; Adiyono, Adiyono (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2025)
This study aims to explore how multicultural education from an Islamic perspective contributes to building intercultural tolerance in Indonesian primary schools. The research was conducted at SDN Pace 01 in the Silo District of Jember Regency using a qualitative case study design. Participants included teachers, students, parents, and the principal. This case study design was chosen because it allows researchers to deeply explore the processes, interactions, and specific contexts of the school as a cohesive system. Data were collected through semi-structured interviews, classroom observations, student surveys, and document analysis. The data were analyzed using Miles and Huberman's interactive model alongside thematic analysis. The findings reveal that Islamic values such as tasamuh (tolerance), ukhuwah (brotherhood), and adl (justice) are consistently integrated into pedagogical practices, including collaborative learning, storytelling, and reflective classroom discussions. Students demonstrated high levels of tolerance toward linguistic, ethnic, and religious diversity, with collaboration emerging as the strongest indicator of this tolerance. However, challenges include limited teacher training in multicultural pedagogy and parental concerns about maintaining Islamic identity. The study concludes that Islamic-based multicultural education provides a practical framework for fostering intercultural competence from an early age while preserving religious identity. The results have significant implications for teacher professional development, curriculum innovation, and community engagement, and suggest directions for future research across broader contexts and with the integration of digital learning platforms.